2021
DOI: 10.25046/aj060236
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded Theory Approach to Digital Transformation in the Postal Sector in Southern Africa

Abstract: This paper describes a qualitative research design adopted in this study guided by deployment of a Grounded Theory (GT) methodology which was deployed to synthesize literature on technology adoption and digital transformation with an objective of developing theory. The philosophical worldview adopted was interpretivism/constructivist of a qualitative grounded theory inductive (theory building) approach where secondary data was sourced from industry reports and related academic peer reviewed literature. The gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The emergent approach in Grounded Theory is achieved by passing through three main steps of coding: open coding (freely coding the text of the interviews or other data to find the main category), selective coding (coding focused on the main category) -these first two steps are called substantive coding -and theoretical coding (connecting the main category to other selected categories) (Chun Tie, Birks & Francis, 2019). In the Grounded Theory method, data collection and open coding co-occur (Mokgohloa et al, 2021). In fact, the open coding process begins after the completion of the first interview; the data are analyzed and a label is considered for each one (Charmaz & Thornberg, 2021); then they are conceptually grouped, and finally basic codes (categories and their characteristics) are produced as the output of this stage.…”
Section: Methodsmentioning
confidence: 99%
“…The emergent approach in Grounded Theory is achieved by passing through three main steps of coding: open coding (freely coding the text of the interviews or other data to find the main category), selective coding (coding focused on the main category) -these first two steps are called substantive coding -and theoretical coding (connecting the main category to other selected categories) (Chun Tie, Birks & Francis, 2019). In the Grounded Theory method, data collection and open coding co-occur (Mokgohloa et al, 2021). In fact, the open coding process begins after the completion of the first interview; the data are analyzed and a label is considered for each one (Charmaz & Thornberg, 2021); then they are conceptually grouped, and finally basic codes (categories and their characteristics) are produced as the output of this stage.…”
Section: Methodsmentioning
confidence: 99%
“…Mokgohloa et al [10], in their earlier research paper, developed ten dimensions that emerged after the saturation of data was reached through a thorough grounded theory (GT) technique. The ten dimensions that emerged during the GT process were (i) digital culture, (ii) digital investments, (iii) operational excellence, (iv) ecosystem capability, (v) adoption, (vi) competitiveness, (vii) digital capabilities, (viii) shared vision, (ix) customer insights, and (x) diverging interests.…”
Section: Methodsmentioning
confidence: 99%
“…Mokgohloa et al [13] identified ten postal digital transformation variables at work in a dynamic setting in Southern Africa: digital ecosystem capability, adoption, shared vision maturity, digital culture maturity, customer insights, diverging interests, operational excellence capability, digital investment capability, digital capabilities, and digital competitiveness capability. The research aims to understand the dynamic feedbacks between these variables by defining a dynamic hypothesis through the articulation of system boundary and development influence diagrams or causal loop diagrams.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their research paper, entitled "Grounded theory (GT) approach to digital transformation in the postal sector in Southern Africa", Mokgohloa et al [13] applied a grounded theory approach to synthesise the literature on technology adoption and digital transformation to develop their theory. The authors applied the GT approach to synthesise data, resulting in the emergent dimensions that described digital transformation and technology adoption in the postal sector in Southern Africa.…”
Section: Postal Dynamics Variablesmentioning
confidence: 99%